Dominance of gluonic scale anomaly in confining pressure inside nucleon and D-term - Daisuke Fujii; Mamiya Kawaguchi; Mitsuru Tanaka (Physics Letters B)
We explore the confining pressure inside the nucleon and the related gravitational form factor referred to as the D-term, using the skyrmion approach based on the scale-invariant chiral perturbation theory, where the skyrmion is described as the nucleon and a scalar meson couples to the scale anomaly through the low energy theorem. Within this model framework, the current quark mass and gluonic quantum contributions to the scale anomaly can be described by the pion and scalar meson masses, respectively, through matching with the underlying QCD. By considering the decomposition of the energy momentum tensor of nucleon, we examine the role of the scale anomaly contributions in the pressure inside the nucleon. As a result, the gluonic scale anomaly is found to dominate the confining pressure. Compared to the result based on the conventional chiral perturbation theory in the chiral limit, our result for the total pressure is capable of qualitatively improving the alignment with lattice QCD observations. Moreover, the pressure from the gluonic scale anomaly is widely distributed in position space, leading to its substantial contribution to the D-term.